2018
DOI: 10.1007/s11684-017-0577-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of chemerin/CMKLR1 in the maintenance of early pregnancy

Abstract: Chemerin is a cytokine that attracts much attention in the reproductive process. This study aimed to explore the effects of chemerin and its receptor chemokine-like receptor 1 (CMKLR1) on the maintenance of early pregnancy. The expression levels of chemerin and CMKLR1 in the decidua tissues of 20 early normal pregnant women and 20 early spontaneous abortion women were examined byWestern blot and real-time polymerase chain reaction analyses. CMKLR1 receptor antagonist (α-NETA) was then intrauterinely injected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…To analyze the regulatory activity of chemerin in the maintenance of early pregnancy, Yang et al assessed the expression of chemerin and its receptors in the decidua tissues from women with spontaneous and planned selective abortions. They discovered the significantly increased chemerin expression and downregulated expression of its receptors (chemokine-like receptor-1 (CMKLR1)) in patients with spontaneous abortions [205]. The intrauterine injection of chemerin receptors' antagonist resulted in a higher rate of embryo resorption in mice and lower ERK1/2 phosphorylation rate in uterine tissue [205].…”
Section: Other Gestational Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the regulatory activity of chemerin in the maintenance of early pregnancy, Yang et al assessed the expression of chemerin and its receptors in the decidua tissues from women with spontaneous and planned selective abortions. They discovered the significantly increased chemerin expression and downregulated expression of its receptors (chemokine-like receptor-1 (CMKLR1)) in patients with spontaneous abortions [205]. The intrauterine injection of chemerin receptors' antagonist resulted in a higher rate of embryo resorption in mice and lower ERK1/2 phosphorylation rate in uterine tissue [205].…”
Section: Other Gestational Complicationsmentioning
confidence: 99%
“…They discovered the significantly increased chemerin expression and downregulated expression of its receptors (chemokine-like receptor-1 (CMKLR1)) in patients with spontaneous abortions [205]. The intrauterine injection of chemerin receptors' antagonist resulted in a higher rate of embryo resorption in mice and lower ERK1/2 phosphorylation rate in uterine tissue [205]. Interestingly, they also described the association between the pre-pregnancy serum chemerin levels and the risk of spontaneous abortion in women with polycystic ovary syndrome (PCOS).…”
Section: Other Gestational Complicationsmentioning
confidence: 99%
“…Furthermore, the calculated single dose LD 50 for α-NETA was 873 mg/kg, which by comparison is safer than caffeine (LD 50 367 mg/kg) 34 . A recent study reported that direct α-NETA injection (5 μg) into the uterine horn on days 6, 9 and 12 following fertilization resulted in significant embryo resorption, thus potentially contraindicating α-NETA for treatment during pregnancy 35 .…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence suggests that chemerin may be responsible for the control of reproductive functions. It has been indicated that the inhibition of the chemerin signaling via the CMKLR1 receptor in the mice decidua results in embryo abortion [ 12 ]. Furthermore, it has been observed that in women who had early spontaneous abortions, the concentrations of chemerin in the blood plasma were decreased, whereas the expression of CMKLR1 in the decidua was found to be elevated [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been indicated that the inhibition of the chemerin signaling via the CMKLR1 receptor in the mice decidua results in embryo abortion [ 12 ]. Furthermore, it has been observed that in women who had early spontaneous abortions, the concentrations of chemerin in the blood plasma were decreased, whereas the expression of CMKLR1 in the decidua was found to be elevated [ 12 ]. The expression of the chemerin system (a collective term for chemerin and its receptors) was confirmed in brain structures responsible for reproductive functions, as well as in the lower branches of the hypothalamic-pituitary-ovarian axis and the female reproductive tract.…”
Section: Introductionmentioning
confidence: 99%